Financial Development and Growth: evidence from Serbia - Božović, Miloš (Industrija, 2019)
This paper studies the relationship between financial development and economic growth in Serbia. We focus on the influence of stock market and banking-sector development on growth. Using the framework of a neoclassical growth model, we investigate the impact of stock market liquidity and credit activity of banks on per-capita GDP growth rate. In lines with many previous results in the literature, we find a positive and statistically significant impact of stock market liquidity and bank credit on economic growth. We control for the usual determinants of growth, such as government consumption, foreign direct investments and inflation.
Keywords: Transition economies; Stock Market; Economic Growth; Bank